Analysis of Simple Society Education and Modern Society Education - Tomi Putra; Firman; Dina Sukma (Aslim: Journal of Education and Islamic Studies, 2025)
This study aims to analyze the differences and similarities between education in simple societies and modern societies, as well as their implications for developing an inclusive education system. Education in simple societies tends to be tradition-based, informal, and oriented toward the practical needs of the community. Meanwhile, education in modern societies is more formal, structured, and technology-based, aiming to create globally competitive human resources. A qualitative approach with a case study method was employed to examine two communities as representatives of each category. Data were collected through interviews, participatory observations, and document analysis. The results of the study show that simple societies emphasize the transmission of cultural values and life skills, while modern societies focus on academic achievement and technological innovation. However, both share the common goal of recognizing the importance of education in building social identity and community sustainability. The study recommends integrating local values from simple societies into modern curricula to create education that is both relevant and contextual.